2020
DOI: 10.3389/fchem.2020.00209
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Anticancer Potential of Benzothiazole-Based Metallacycles

Abstract: A series of 2-phenylbenzothiazole derivatives and their corresponding organometallic ruthenium(II) and osmium(II) complexes were synthesized, designed to exploit both, the attributes of the half-sandwich transition metal scaffold and the bioactivity spectrum of the applied 2-phenylbenzothiazoles. All synthesized compounds were characterized via standard analytical methods. The obtained organometallics showed antiproliferative activity in the low µM range and are thus at least an order of magnitude more potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A similar trend was observed with the related 4-phenyltriazole based Ru(II)and Os(II)-arene compounds by Riedl et al 15 The metal-chlorido bond lengths (2.4124(11)-2.4232(6) Å) are consistent with anticipated values. 15,25,[34][35][36]…”
Section: Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar trend was observed with the related 4-phenyltriazole based Ru(II)and Os(II)-arene compounds by Riedl et al 15 The metal-chlorido bond lengths (2.4124(11)-2.4232(6) Å) are consistent with anticipated values. 15,25,[34][35][36]…”
Section: Characterizationmentioning
confidence: 99%
“…The chloride-ion affinity of 2a and 2c was investigated via UV-Vis spectroscopy at various KCl concentrations at 25 °C…”
Section: Chloride Ion Affinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1a has a benzothiazole ring, which is analogous to other compounds with a 5-membered ring fused to benzene, such as indoles, benzimidazoles, benzofurans, and benzothiophenes, and these structures are widely used by medicinal chemists as scaffolds. Studies have shown that 2-arylbenzothiazole derivatives have diverse biological activities [ 23 ], such as antibacterial [ 24 , 25 , 26 ], anticancer [ 27 , 28 , 29 , 30 ], antioxidant [ 31 ], anti-tuberculosis [ 32 ], neuroprotective [ 33 ], hyaluronidase inhibitory [ 34 ], and antifungal properties [ 35 ]. In addition, the 2-arylbenzothiazole scaffold is found in various drugs, such as zopolrestat, pramipexole, ethoxazolamide, and entaluron.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that 2-arylbenzothiazole derivatives have diverse biological activities [23], such as antibacterial [24][25][26], anticancer [27][28][29][30], antioxidant [31], anti-tuberculosis [32], neuroprotective [33], hyaluronidase inhibitory [34], and antifungal properties [35]. We synthesized a series of 16 derivatives of compound 1a and examined their tyrosinase inhibitory activities using mushroom and murine cellular tyrosinase, and their antimelanogenic effects in murine B16F10 cells.…”
Section: Introductionmentioning
confidence: 99%